Impact of Anaemia on the Severity of Acute Bronchiolitis in Infants - Çelik Elif; Çelik, Serkan Fazlı; Güngör, Şükrü; Dursun, Adem (Journal of Nepal Paediatric Society, 2021)
Introduction: Although anaemia is a predisposing factor in the occurrence of lower respiratory tract infections, there is limited data about the relationship between anaemia and acute bronchiolitis in infants. The aim of this study is to determine whether anaemia is an independent clinical condition increasing the severity of acute bronchiolitis in infants. Methods: This retrospective study was conducted on 163 infants (101 acute bronchiolitis and age and sex matched 62 controls), aged between one month to two years. According to the clinical severity of the disease, patients were divided as having mild, moderate and severe acute bronchiolitis. Haemoglobin (Hb) level was considered low when below 11 gm/dL, which is less than 2 standard deviation (SD). Results: Median Hb and mean cell haemoglobin concentration (MCHC) levels were significantly lower in acute bronchiolitis patients than controls 10.1 gm/dL (9.6 - 10.6 gm/dL) vs. 11.2 gm/dL (10.6 - 12.1 gm/dL); p < 0.001), and 33.6 (32.5 - 34.1 gm/dL) vs. 34 gm/dL (33.1 - 34.5 gm/dL) p = 0.012. Conversely, median red cell distribution width (RDW) was higher 14.4% (13.5 - 15.6%) vs. 14.1% (13.1-15%). When evaluated by logistic regression analysis, the risk of severe bronchiolitis increased 10 times in acute bronchiolitis patients with a Hb value ≤ 10 gm/dL. Also, there was a significant negative correlation between Hb level and bronchiolitis severity (r :- 0.423, p < 0.001). Furthermore, the patients who had Hb value under 9.95 gm/dL had risk of more severe bronchiolitis with 73.7% sensitivity and 83.3% specificity than other patients. Conclusions: Anaemic infants are more susceptible to acute bronchiolits and as the degree of anaemia increases, they are more severely affected.